2019
DOI: 10.1096/fj.201802297r
|View full text |Cite
|
Sign up to set email alerts
|

Increasing availability of ω‐3 fatty acid in the early‐life diet prevents the early‐life stress‐induced cognitive impairments without affecting metabolic alterations

Abstract: Exposure to early‐life stress (ES) is associated with cognitive and metabolic deficits in adulthood. The role of early nutrition in programming these long‐term effects is largely unknown. We focused on essential ω‐3 and ω‐6 long‐chain polyunsaturated fatty acids (LCPUFA) and investigated whether ES affects central and peripheral FA profiles, as well as if and how an early diet with increased availability of ω‐3 LCPUFA (via lowering ω‐6/ω‐3 ratio) protects against ES‐induced impairments. ES exposure [limited ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
99
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(115 citation statements)
references
References 84 publications
(98 reference statements)
12
99
2
1
Order By: Relevance
“…Consistent with the behavioral outcomes found in adulthood, early-life supplementation of ω-3 has been shown to prevent increases in anxiety-like and depression-like behavior following ELS [152,153]. Moreover, ω-3 fatty acid supplementation during gestation and early life has been shown to prevent alterations to the development of microglia in the HIP, while also reducing cognitive deficits following ELS [55,154].…”
Section: Early Preventative Interventionssupporting
confidence: 53%
See 2 more Smart Citations
“…Consistent with the behavioral outcomes found in adulthood, early-life supplementation of ω-3 has been shown to prevent increases in anxiety-like and depression-like behavior following ELS [152,153]. Moreover, ω-3 fatty acid supplementation during gestation and early life has been shown to prevent alterations to the development of microglia in the HIP, while also reducing cognitive deficits following ELS [55,154].…”
Section: Early Preventative Interventionssupporting
confidence: 53%
“…Early effects comprise reduced processes complexity in the HIP, suggesting the presence of an amoeboid phenotype and reduced number in the entorhinal cortex [56]. However, the late effects of this paradigm have not been reported if not in combination with another early environmental manipulation (unbalanced fatty acid diet), in which limited bedding induced an increase in microglia in the adult HIP [55]. A series of ex vivo investigations on the early effects of maternal separation (MS) on microglia showed a general increase in the proportion of cells with an activated morphology (amoeboid/hypertrophic, with large somas and thick short processes) across central nervous system (CNS) regions such as the HIP [57][58][59] and the medulla [60].…”
Section: Postnatal Behavioral Stressorsmentioning
confidence: 89%
See 1 more Smart Citation
“…The quality of nutrition early in life is increasingly acknowledged as an important determinant of later-life health [20,21], and negative health outcomes induced by ES or WSD are potentially modified by early life diet. Nutritional interventions during infancy and childhood may therefore be considered as potential therapeutic strategies to protect against the manifestation of later metabolic problems [22] and to prevent the negative effects of ES on brain structure and function [23,24]. In line with this, exclusivity and duration of breastfeeding, as compared with formula feeding, are positively associated with later-life metabolic profile [25][26][27] and cognitive performance [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increasing DHA content failed to prevent some of the impairments in the brain fatty acid profile that were induced by the high supply of LA (Novak et al, 2008). Rodent studies have shown that lowering the postnatal dietary LA supply can stimulate brain DHA accumulation (Schipper et al, 2016a), alter the structural development of neuronal networks (Schipper et al, 2013) and protect the developing brain against early life stress-induced neurocognitive impairments in adulthood (Yam et al, 2019). Due to the persistent changes in, for example, serotonergic and dopaminergic neurotransmitter systems that are linked to early life impaired brain DHA accumulation (Chalon, 2006), it has been hypothesized that the contemporary increase in nutritional supply of LA and low supply of DHA may also contribute to the increased incidence of neurological and psychiatric disorders such as depression and schizophrenia that has been observed over the last decades (Klerman and Weissman, 1989;Muskiet, 2010;McNamara, 2013;Grosso et al, 2014).…”
Section: Dietary Fatty Acids Are Used As Building Blocks For the Devementioning
confidence: 99%